Features of voice traffic transmission using IEEE 802.11ac wireless networks - Lazebnyi, V.S.; Omelyanets , O.O. (Radiotekhnika, 2024)
The purpose of the research is to find out the features of voice traffic transmission for the organization of IP telephony service in office premises using the IEEE 802.11ac network to ensure the high-quality provision of the specified service for a sufficiently large number of users even in the case of intensive transmission of a mixed traffic. The analytical study is based on traditional probabilistic approaches to evaluating the operational characteristics of wireless networks of the 802.11 standard. The 802.11ac network with a channel bandwidth of 20 MHz in the mode with one spatial stream was studied. In the specified network, a scenario was considered in which, for the provision of IP-telephony services, prioritization was carried out in accordance with the IEEE 802.11e specification, with AC_VO priority given to a voice traffic, and AC_BK priority to other data transmitted over the same network. It is mathematically substantiated that if there are stations in the IEEE 802.11ac network transmitting low-priority traffic of the AS_BK class, even under saturated load conditions, the simultaneous operation of a large number of stations transmitting voice traffic is possible. Estimates of the effect of frame sizes of low-priority traffic, as well as the impact of collisions on conditions of voice traffic transmission are obtained. The work uses an original method of studying the conditions of transmission of high-priority traffic in networks with a mixed load. The research results will be useful to specialists in the field of planning and maintenance of IEEE 802.11 wireless networks to ensure high quality indicators of voice services.